Characterization of a Model of Laminopathies in Juvenile and Young Adult Zebrafish - Tan, Qin Tai (Université d'Ottawa / University of Ottawa, 2025)
We previously reported the generation of a zebrafish mutant (lmna⁻ᐟ⁻) for the lamin A/C gene that presents with skeletal muscle defects during the first week post fertilization and mild and transient cardiac defects. The phenotype analysis at the early stages of development suggested that this mutant could serve as a model for striated muscle laminopathy. In humans, striated muscle laminopathies often start at a young age, and progress into adulthood. It may be that the defects reported in lmna⁻ᐟ⁻ also progress into adulthood in a similar manner. In this study, we examined cardiac and skeletal muscles in juvenile and young adult zebrafish, to determine if this is the case. Heart rate analysis shows cardiac defects such as bradycardia and arrhythmia, starting at 2 months post fertilization in homozygous (lmna⁻ᐟ⁻) mutants compared to wild type siblings (lmna⁺ᐟ⁺). Ultrasound analysis reveals a lower E/A ratio and a lower fractional shortening of the lmna⁻ᐟ⁻ juvenile and young adult compared to lmna⁺ᐟ⁺. These juvenile and young adult fish also show swim ability defects but without any apparent defect in trunk muscle. These results further confirm the usefulness of this model in studying striated muscle laminopathies into adulthood, for various purposes such as small molecule testing for phenotype rescue.
Keywords: Striated muscle laminopathies; Zebrafish; Lmna